Assessing Improvement of Facial Appearance and Quality of Life after Minimally-Invasive Cosmetic Dermatology Procedures Using the FACE-Q Scales - Hible, Brian P. (J Drugs Dermatol, 2016)
BACKGROUND: Detecting clinically meaningful change from the patients' perspective is critical to evaluating a successful cosmetic procedure. FACE-Q is a patient-reported outcome instrument for use in patients undergoing cosmetic procedures. OBJECTIVE: We sought to determine the impact of laser resurfacing and injectable treatment (neurotoxin or fillers) on patient perceived improvement in facial appearance. METHODS AND MATERIALS: Patients were asked to complete FACE-Q scales (Satisfaction with Facial Appearance, Satisfaction with Facial Skin, and Appraisal of Facial Lines) at their pre-procedure consultation and/or at post-procedural follow-up. Item means (range 1-4) and Rasch transformed scores (range 0-100) were compared pre to post-procedure using two sample t-tests. Higher FACE-Q scores indicated greater satisfaction. RESULTS: Overall, patients experienced a statistically significant improvement in all three scales pre- to post-procedure (P <0.05). Subgroup analysis showed statistically significant improvement in Satisfaction with Facial Appearance and Satisfaction with Facial Skin for both the laser resurfacing group and injectables group with moderate effect sizes. Improvement on Appraisal of Facial Lines trended toward improvement but did not reach statistical significance. CONCLUSION: Our results support the ability to directly measure and quantify meaningful improvement in appearance among facial cosmetic dermatology patients using FACE-Q scales. Reporting this data is important, as this is the first step towards evidence-based cosmetic procedures in dermatology.